Awareness of radiation protection and dose levels of imaging procedures among medical students, radiography students, and radiology residents at an academic hospital: Results of a comprehensive survey. Issue 86 (January 2017) - Faggioni, Lorenzo; Paolicchi, Fabio; Bastiani, Luca; Guido, Davide; Caramella, Davide
Highlights: Medical students tend to overstate their knowledge of radiation protection (RP). Overall RP knowledge of young doctors and students is suboptimal. RP teaching to undergraduates and postgraduates needs to be substantially improved. Abstract: Purpose: To evaluate the awareness of radiation protection issues and the knowledge of dose levels of imaging procedures among medical students, radiology residents, and radiography students at an academic hospital. Material and methods: A total of 159 young doctors and students (including 60 radiology residents, 56 medical students, and 43 radiography students) were issued a questionnaire consisting of 16 multiple choice questions divided into three separated sections (i.e., demographic data, awareness about radiation protection issues, and knowledge about radiation dose levels of common radiological examinations). Results: Medical students claimed to have at least a good knowledge of radiation protection issues more frequently than radiology residents and radiography students (94.4% vs 55% and 35.7%, respectively; P < 0.05), with no cases of perceived excellent knowledge among radiography students. However, the actual knowledge of essential radiation protection topics such as regulations, patient and tissue susceptibility to radiation damage, professional radiation risk and dose optimisation, as well as of radiation doses delivered by common radiological procedures was significantly worse among medical students than radiology residents and radiography students (P < 0.05). Those latter significantly outperformed radiology residents as to knowledge of radiation protection issues (P < 0.01). Overall, less than 50% of survey respondents correctly answered all questions of the survey. Conclusions: Radiology residents, radiography students and medical students have a limited awareness about radiation protection, with a specific gap of knowledge concerning real radiation doses of daily radiological examinations. Both undergraduate and postgraduate teaching needs to be effectively implemented with radiation safety courses.